2021
DOI: 10.5194/acp-21-10005-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Emissions of intermediate-volatility organic compounds from vehicles under real-world driving conditions in an urban tunnel

Abstract: Abstract. Intermediate-volatility organic compounds (IVOCs) emitted from vehicles are important precursors to secondary organic aerosols (SOAs) in urban areas, yet vehicular emission of IVOCs, particularly from on-road fleets, is poorly understood. Here we initiated a field campaign to collect IVOCs with sorption tubes at both the inlet and the outlet in a busy urban tunnel (>30 000 vehicles per day) in south China for characterizing emissions of IVOCs from on-road vehicles. The average emission factor of I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The updated emission inventory shows that ambient S/IVOCs in Guangzhou was mainly contributed by vehicle emissions (45%) and industry (38%) . A recent local tunnel study in Guangzhou suggested the ambient IVOCs from vehicle emission was dominated by gasoline vehicles (80%) . If we assume that ambient cyclic and linear alkane concentrations in Guangzhou are present in similar ratios as emitted by gasoline vehicles, then the total SOA contribution from linear and cyclic alkanes increases from 8 to 20% (linear only) to 17.5–46%.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The updated emission inventory shows that ambient S/IVOCs in Guangzhou was mainly contributed by vehicle emissions (45%) and industry (38%) . A recent local tunnel study in Guangzhou suggested the ambient IVOCs from vehicle emission was dominated by gasoline vehicles (80%) . If we assume that ambient cyclic and linear alkane concentrations in Guangzhou are present in similar ratios as emitted by gasoline vehicles, then the total SOA contribution from linear and cyclic alkanes increases from 8 to 20% (linear only) to 17.5–46%.…”
Section: Resultsmentioning
confidence: 98%
“…84 A recent local tunnel study in Guangzhou suggested the ambient IVOCs from vehicle emission was dominated by gasoline vehicles (80%). 85 If we assume that ambient cyclic and linear alkane concentrations in Guangzhou are present in similar ratios as emitted by gasoline vehicles, then the total SOA contribution from linear and cyclic alkanes increases from 8 to 20% (linear only) to 17.5−46%. The updated IVOC contribution to SOA is comparable to the traditional VOCs (13−68%) when different SOA yields were applied, as shown in Figure 4c.…”
Section: Comparison Betweenmentioning
confidence: 99%
“…The produced species are oxygenated SecVOC2 and OOA2, showing enhancement with O x , peaking at midday to the afternoon. This process was rapid, as the SOA production increased by a factor of 2.5 and the oxygenated VOCs production increased by a factor of 1.7 within 6 h. The traffic VOCs are widely observed to contribute to SOA production, with aromatic compounds serving as key precursors (Fang et al, 2021). The semi-volatile nature of HOA means it could be evaporated to the gas phase and further oxidized to recondense as SOA (Robinson et al, 2007).…”
Section: Oxidation Process Of Organics In the Day And Nightmentioning
confidence: 99%
“…This process was rapid as the SOA production by a factor of 2.5 and the oxygenated VOCs production by a factor of 1.7 within 6 hours. The traffic VOCs are widely observed to contribute to SOA production, with aromatic compounds serving as key precursors (Fang et al, 2021).…”
Section: Oxidation Process Of Organics In the Day And Night 253mentioning
confidence: 99%